2011
DOI: 10.1177/1741826711410517
|View full text |Cite
|
Sign up to set email alerts
|

Normal values for cardiopulmonary exercise testing in children

Abstract: Background: A reference set of data of normal values of newly developed cardiopulmonary parameters of exercise testing in an 8-18-year-old population is lacking. Patients and methods: Cardiopulmonary exercise testing was performed in 175 healthy school children (8-18 years old). Continuous electrocardiography was performed, and minute ventilation, oxygen uptake (VO 2 ), and carbon dioxide (CO 2 ) production were measured continuously with a respiratory gas analysis system. Results: Peak VO 2 /kg did not change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
53
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(60 citation statements)
references
References 11 publications
6
53
0
1
Order By: Relevance
“…From these exercise tests, maximum oxygen uptake (VO 2 peak) and ventilatory efficiency (VE/VCO 2 slope) were assessed and expressed as percentage of predicted values. To calculate the predicted values, norm values from healthy children were used [25].…”
Section: Exercise Testingmentioning
confidence: 99%
“…From these exercise tests, maximum oxygen uptake (VO 2 peak) and ventilatory efficiency (VE/VCO 2 slope) were assessed and expressed as percentage of predicted values. To calculate the predicted values, norm values from healthy children were used [25].…”
Section: Exercise Testingmentioning
confidence: 99%
“…Age, sex and height are strongly associated with exercise time, heart rate and oxygen uptake. While reference values for cardiopulmonary parameters of exercise testing in children are available in some ethnic groups [47][48][49], they are currently lacking in Indian children. This test will help determine a passenger's requirement for supplemental oxygen in a flight.…”
Section: Cardiopulmonary Exercise Testing (Cpet)mentioning
confidence: 98%
“…The test is also more sensitive for detecting early or subclinical disease than less comprehensive tests that are done at rest [46]. CPET can be safely and effectively performed in children, even as young as 5 y of age [47][48][49]. Age, sex and height are strongly associated with exercise time, heart rate and oxygen uptake.…”
Section: Cardiopulmonary Exercise Testing (Cpet)mentioning
confidence: 99%
“…It is important to provide reference values for cardiovascular fitness and responses of heart rate (HR) and systolic blood pressure (SBP) to maximal exercise test in children to be able to evaluate the cardiovascular function and health of children and to detect those with abnormal values (Paridon et al, 2006). Although there are a few population studies on cardiovascular fitness or haemodynamic responses to maximal exercise test in healthy children (Dencker et al, 2008;Eiberg et al, 2005;Ten Harkel, Takken, Van Osch-Gevers, & Helbing, 2011), none of them have reported cardiovascular fitness and changes in HR and SBP during and after exercise test.…”
Section: Introductionmentioning
confidence: 94%